A PRELIMINARY STUDY ON THE GROWTH AND FOOD OF STOLEPHORUS SPP. FROM THE JAKARTA BAY - Burhanuddin, -; Martosewojo, Sularto; Hutomo, Malikusworo (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1975)
The length compositions of Stolephorus heterolobus, Stolephorus insularis and Stolephorus pseudoheterolobus were observed. S. heterolobus ranged from 25 to 71 mm., S. insularis from 27 to 75 mm and S. pseudoheterolobus from 27 to 67 mm standard length. The ages of these three species were estimated. The asymptotic length of S. heterolobus was 97 mm attained at the age of 26 months, S. insularis 86 mm at 26 months and S. pseudohetorolobus 88 mm at 20 months. The highest growth rate of S. heterolobus was at the size group 30 - 80 mm standard length, that of S. insularis was at 30-50 mm, and that of S. insularis was observed to be the lowest. The stomach contents of S. heterolobus and S. pseudoheterolobus were studied tand were found that the food of these two species was more or less the same. They fed mainly on zooplankton consisting of copepods and other crustaceans.